Effects of polyethylene terephthalate (PET) microplastics and acid rain on physiology and growth of Lepidium sativum. (1st August 2021) - Pignattelli, Sara; Broccoli, Andrea; Piccardo, Manuela; Terlizzi, Antonio; Renzi, Monia
Abstract: This study evaluated the chronic toxicity (30 days) of different sizes of polyethylene terephthalate (PET) microplastics (60–3000 μm) provided alone or in combination with acid rain, on garden cress ( Lepidium sativum ) . Both biometrical and physiological traits have been evaluated: i) percentage inhibition of seed germination, plant height, leaf number and fresh biomass production; ii) oxidative stress responses (hydrogen peroxide; ascorbic acid and glutathione production); iii) impairment in photosynthetic machinery in term of pigments production; iv) aminolevulinic acid and proline production. Results highlighted that different sizes of PET, alone or in combination with acid rain, are able to negatively affect both biometrical and physiological plant traits. In particular, the lower size of microplastics is able to negatively affect growth and development, as well as to trigger the oxidative burst. Regarding the pigments production, PET coupled with acid rain, induced a higher production of Chl-b, and an inhibition of aminolevulinic acid. Graphical abstract: Image 1 Highlights: L. sativum was exposed to PET alone or coupled with acid rain. Lower size of PET most negatively affects growth and development of garden cress. PET alone or coupled with acid rain triggers oxidative burst. PET with acid rain negatively affect: AsA, Chl a and AlA productions. Higher AlA values correspond to higher proline values. Abstract : PET microplastics (60–3000 μm), alone or in combination with acid rain, are able to negatively affect both biometry and physiology of L. sativum, depending to different particle size.